Literature Study of Three Plant Formulations with Anti-Candida Albicans Activity in Feminine Liquid Soap Preparations - Tatiana Siska Wardani; Kusumaningtyas Siwi Artini; Ilham Latansa (Proceeding of International Conference on Science, Health, And Technology, 2021)
Candida albicans is a fungus that causes vaginal discharge in women. Leucorrhoea is a discharge from the vagina with a relatively small frequency, odorless, and clear. In Indonesia, there are many plants that have medicinal properties that are used in traditional medicine and are believed to have antifungal activities.Feminine hygiene soap is a liquid cleansing preparation for femininity which is made from basic ingredients and is used to clean the feminine area without causing irritation to the skin.This study aims to provide information about plants that have anti-fungal activity and their formulation as a good female liquid soap preparation with their activity as an anti-candida albicans. The method in this research is by searching literature studies from various journals. The results showed that each female liquid soap preparation with plants as the active substance gave different inhibition diameters. The difference between the active substance and the additive in the formulation affects the resulting inhibition diameter. Based on the results of a literature review, basil,cabbage (Brassica oleracea var. capitata alba) and waru (Hibiscus tiliaceus), has activity as an antifungal against Candida albicans.